(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2019)
This study addresses the issue of implementing a system approach during the higher school specialists preparation, which effectively leads to their professional competence formation. The study results of higher education teachers professional difficulties in the interaction with the educational process participants are presented. The training technology on the system approach basis creates conditions for the learning process participants’ activities systemic organization, as well as for the system thinking skills and the system approach developing in cognitive, practical and other ongoing and forthcoming activities. An important factor in the future specialists’ professional competence formation is an indicative basis formation for their future professional activity. The professional competence structure and components characteristic are given. Examples are also presented, that demonstrate the professional competence formation implementation with a focus on current society needs. There is a description of the students’ considerable professional competence increase after its formation methods correction.